Performa Inhibitory Control dengan Induksi Sing-a-Song Stress Test pada Dewasa Awal - Kurniawan, Akhmad; Kusrohmaniah, Sri (Faculty of Psychology, Universitas Gadjah Mada, 2018)
Inhibitory control is able to control attention by inhibiting internal tendencies and external influences. Inhibitory control is controlled by dorsolateral prefrontal cortex and anterior cingulate cortex, that can be affected by stress variable. Sing-a-Song Stress Test (SSST) is a current method to induce stress that has never been practiced in the study of inhibitory control. This study aimed to determine the effect of SSST against inhibitory control in the early adult. Between subjects, the design was applied in this study. A number of 35 participants with an age range from 17 to 21 years old were randomly assigned into an experimental group (n = 17) and control group (n = 18). Inhibitory control was measured using the Computerized Stroop Color-Word Test (CSCWT). Positive Affect and Negative Affect Schedule (PANAS) was used to conduct a manipulation check. Independent-Samples T Test explained no significant effect of stress on inhibitory control (t = -0,117; p > 0,05).Â Abstrak. Inhibitory control berfungsi untuk mengontrol atensi dengan cara menghambat kecenderungan internal dan pengaruh eksternal. Inhibitory control dikendalikan oleh dorsolateral prefrontal cortex dan anterior cingulate cortex, yang dapat dipengaruhi oleh variabel stres. Sing-a-Song Stress Test (SSST) merupakan metode baru dalam induksi stres yang belum pernah diterapkan pada penelitian inhibitory control. Penelitian ini bertujuan untuk mengetahui pengaruh SSST terhadap inhibitory control pada dewasa awal. Between subjects design digunakan dalam penelitian ini. Sebanyak 35 partisipan berusia 17 sampai 21 tahun dikelompokkan secara acak ke dalam kelompok eksperimen (n = 17) dan kelompok kontrol (n = 18). Inhibitory control diukur melalui Computerized Stroop Color-Word Test (CSCWT). Positive Affect and Negative Affect Schedule (PANAS) digunakan untuk melakukan cek manipulasi. Independent-Samples T Test menunjukkan adanya pengaruh yang tidak signifikan antara stres dan inhibitory control (t = -0,117; p > 0,05).